Comparison of the dynamics of bone tissue quality and mineral composition of the femoral neck in rats during different periods of experimental hypokinesia - Dovgan , R.R.; Masna , Z.Z. (Морфологія / Morphologia / Morfologìâ, 2025)
Relevance. Hypokinesia is one of the serious problems of the modern lifestyle. Its impact on the musculoskeletal system manifests as muscle atrophy, impairment of the joint ligamentous apparatus structure, and decrease in bone mass — therefore, a sedentary lifestyle is recognized as a risk factor for osteoporosis development. Aim. To determine the dynamics of changes in the quality and mineral composition of the femoral neck bone tissue under conditions of forced limb immobilization in the experiment. Methods. To identify the dynamics of changes developing against the background of forced immobilization, an experimental study was conducted on 25 adult male outbred white rats aged 3–3.5 months and weighing 180–200 g. Forced experimental hypokinesia was modeled by immobilizing the hind limbs with a plaster cast of the coxite type (reinforced with a metal wire), completely restricting movement in the hip and knee joints. The observation periods were 3, 4, 5, and 6 weeks. Bone tissue density was determined in conditional grayscale units (GSU) using a radiovisiographic study on a Siemens device with TROPHI Radiologi software. The content of mineral elements in the femoral neck bone tissue was determined in mg/g by atomic absorption spectral analysis performed on an AAS-1N atomic absorption spectrophotometer (Carl Zeiss Jena, Germany) using a propane-butane-air flame. Results. After 6 weeks of the experiment, bone tissue density of the femoral neck in rats decreased by 3% compared to the control. The study of mineral content in the bone tissue throughout six weeks revealed distinct dynamics characteristic of each element. By the end of the experiment, calcium, sodium, zinc, and strontium levels were higher than in intact animals, whereas phosphorus and magnesium levels were lower, and lead content remained unchanged compared to normal values. The study of bone density dynamics and the absolute values of macro- and microelement content in bone tissue under prolonged experimental experimental hypokinesia allows for a better understanding of the causes of structural and mechanical alterations of bone under forced motion restriction and can contribute to the development of effective methods of prevention and correction.